URGENSI PENGAWASAN DALAM PENYUSUNAN DPTb DAN DPK MENGAHADAPI PEMILU 2024 DI BAWASLU PADANG PARIAMAN - Rahayu, Zona Rida; Permata, Riyen (ASOSIASI IDEBAHASA KEPRI, 2024)
DPT (Permanent Voter List) comes from data from the last general election and elections. Through this DPT, the public can actively participate in the 2024 elections. One indicator of the success of the election is high voter participation, because it will provide strong legitimacy to whoever wins and becomes the government. If people are not registered in the DPT, they can propose an Additional Voter List (DPTb) so they can exercise their voting rights. Apart from that, the community also maintains a Special Voter List (DPK), which is a list of voters who have a residency identity but are not yet registered in the DPT and DPTb. For this reason, it is important for the Pariman Regency Bawaslu to supervise the DPTb and DPK proposal stages. Election monitoring strategies that can be carried out in involving the community are (1) Mapping and strengthening participants, (2) Determining appropriate information content, (3) Effective delivery of information, (4) Panwaslu as a facilitator. The methods used in this service are lectures, questions and answers, and discussions. The lecture was carried out in presenting material on forms of supervision that participants can carry out, reading potential problems in determining the DPTb and DPK and providing solutions so that the 2024 resumption runs smoothly. This activity was held on Tuesday 26 August 2023 at the Sambalado Hall, Jalan Zaini, Simpang Kurai Taji Village, Pariaman City.